The European Union's shaping of the international legal order - Kochenov, Dimitry, 1979-; Amtenbrink, Fabian (Cambridge University Press, 2013)
"The European Union undoubtedly plays an important role in the formation of international law. This takes place through a number of avenues ranging from the simple existence of this supranational legal order within the sphere of international law to the actual influencing of international legal order. With contributions by leading scholars, this collection of essays constructs and analyses a new and stimulating approach in which the European Union is perceived as an active co-creator of the international legal order on a variety of planes. Providing concrete examples of the European Union's approach to the international legal order in different policy fields, this book will be a key reference point for a new active paradigm of EU external relations law"--